Does Social Pension Insurance Increase the Efficiency of Household Financial Portfolios? - Xueying Liu; Zhong Zhao (Institute of Labor Economics (IZA), 2024)
This study investigates the impact of social pension insurance on the efficiency of household financial portfolios, utilizing data from the 2019 wave of the China Household Finance Survey. Our findings indicate that social pension insurance significantly enhances the efficiency of household financial portfolios, partly through the channels of risk attitude and precautionary savings.
Keywords: G59; J24; I28; 330; social pension insurance; household portfolios; sharpe ratio; efficiency